The Quest of The Islamic Archipelago Inheritance through The Javanese Living Folklore - Siti Masitoh (el Harakah: Jurnal Budaya Islam, 2016)
This article is aimed at digging out the Islamic archipelago inheritance through the Javanese living folklore namely ruwatan. Ruwatan is the traditional ceremony done in order to pray to God so that the life of sukerta (one carrying bad luck) will not be under the threat of Bathara Kala. God is the only one who is able to release the sukerta‘s burden. The dalang (story teller) functions as a mediator of the sukerta to pray to God. Ruwatan is usually done by performing the shadow play and the dalang narrates Murwakala. There are many activities undergone by both the dalang and the sukerta before and after the performance of the shadow play. This article discusses the message of Murwakala in which the writer believes that it is not against the Islamic belief. It is a matter of fact that Murwakala was created in the 17th century anonymously so it can be assumed that it is related to the arrival of Islam in Java. Artikel ini bertujuan menggali warisan Nusantara Islam melalui cerita rakyat orang Jawa yaitu ruwatan. Ruwatan merupakan upacara adat dalam rangka berdoa kepada Tuhan agar kehidupan sukerta (pihak yang menyandang sesuatu penyebab kesialan) tidak akan berada di bawah ancaman Bathara Kala. Tuhanlah satu-satunya yang mampu melepaskan beban sukerta. Dalang berfungsi sebagai mediator sukerta untuk berdoa kepada-Nya. Ruwatan biasanya dilakukan dengan pertunjukan wayang dan dalang mengisahkan Murwakala. Ada beberapa ritual yang dilakoni baik dalang maupun sukerta sebelum dan setelah pertunjukan wayang. Artikel ini membahas pesan Murwakala di mana penulis berpendapat bahwa pesan tersebut tidak bertentangan dengan keyakinan Islam. Fakta menunjukkan bahwa Murwakala diciptakan pada abad ke-17 secara anonim sehingga dapat diasumsikan bahwa itu terkait dengan masuknya Islam ke tanah Jawa.